2015
DOI: 10.1117/12.2075930
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 1D and 2D LSTM architectures for the recognition of handwritten Arabic

Abstract: In this paper, we present an Arabic handwriting recognition method based on recurrent neural network. We use the Long Short Term Memory (LSTM) architecture, that have proven successful in different printed and handwritten OCR tasks. Applications of LSTM for handwriting recognition employ the two-dimensional architecture to deal with the variations in both vertical and horizontal axis. However, we show that using a simple pre-processing step that normalizes the position and baseline of letters, we can make use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Although recognition methods using MDLSTM could learn both horizontal and vertical representation of a document image and reduce the recognition error caused by distortion, the training process is quite time consuming. M. Yousefi in [5] confirmed that if text line sample is properly preprocessed, 1D LSTM can outperform MDLSTM in handwritten Arabic recognition. They achieved state-of-the-art performance on IFN/ENIT dataset [6], moreover the training speed is fast compared with MDLSTM.…”
Section: Introductionmentioning
confidence: 63%
“…Although recognition methods using MDLSTM could learn both horizontal and vertical representation of a document image and reduce the recognition error caused by distortion, the training process is quite time consuming. M. Yousefi in [5] confirmed that if text line sample is properly preprocessed, 1D LSTM can outperform MDLSTM in handwritten Arabic recognition. They achieved state-of-the-art performance on IFN/ENIT dataset [6], moreover the training speed is fast compared with MDLSTM.…”
Section: Introductionmentioning
confidence: 63%
“…They used the OpenHaRT dataset, and implemented the n-gram language model, which was pre-smoothed using the Modified Kneser-Ney method. Yousefi et al (2015) performed a similar experiment as Chherawala et al (2013). However, in this experiment, they showed that LSTM, which was faster to learn and converge compared to MDLSTM, had also achieved better results in the same IFN/ENIT dataset, with the same handcraft features, namely, CCV, RM, MB, LGH.…”
Section: Arabic Text Recognition With Deep Learningmentioning
confidence: 88%
“…For example, Breuel et al [14] combined a standard 1-D LSTM network architecture with a text line normalization method for performing OCR of printed Latin and Fraktur scripts. In a similar manner, by normalizing the positions and baselines of letters, Yousefi et al [16] achieved superior performance and faster convergence with a 1-D LSTM network over a 2-D variant for Arabic handwriting recognition.…”
Section: Related Workmentioning
confidence: 99%